An in vitro Three-Dimensional Co-Culture System for Ameloblastoma Modelling (Sistem Ko-Kultur Tiga Dimensi secara in vitro untuk Pemodelan Ameloblastoma) - Lee, Soo Leng; Rahman, Zainal Ariff Abdul; Tsujigiwa, Hidetsugu; Hamada, Mei; Takabatake, Kiyofumi; Nakano, Keisuke; Nagatsuka, Hitoshi; Siar, Chong Huat (Penerbit Universiti Kebangsaan Malaysia, 2019)
Ameloblastoma, the most clinically significant odontogenic epithelial tumor, is a locally-invasive and destructive lesion in the jawbones. However, the nature of this infiltrativeness and destructive behavior remains ill-understood. To address this, we established an in vitro three-dimensional (3D) co-culture system to simulate an amelobastoma disease model aimed at investigating the interactions between tumor cells and osteoblasts. Osteoblastic cell lines (KUSA/A1 and mc3T3-E1) and one stromal cell line (ST2) were separately co-seeded with ameloblastoma-derived cell line (AM-1) in a collagen scaffold (representing the extracellular bone matrix) and incubated with mineralization medium. Inununohistochemistry, double immunofluorescence and mineralization assay were performed. Only Am-1/KUsA-A1 co-culture showed a significant increase in Am-1 cell count, suggesting that heterotypic cell-cell interaction promotes tumoral cell growth, while formation of visible Am-1 epithelial nest-like structures resembling ameloblastoma cells in their native state, suggest morphodffferentiation. A RANK-high, RANKL-low and osteoprotegerin-low immunoprofile in co-culture AM-1 cells implies deregulated osteoclastogenesis. Mineralization assays showed diminished calcification in Am-1/KUSA-A1 co-culture extracellular matrix suggesting an altered local bone metabolism. In contrast, KUSA/A1 monocultures showed abundant extracellular matrix calcification. Taken together, these results suggest that a 3D co-culture system as an amelobastoma disease model provides insights that bidirectional ameloblastoma-osteoblastic interactions might play a role in modulating tumor growth and osteoclastogenesis.